Profit, Self-Interest, and Deforestation: A Qualitative Literature Review Through Adam Smith - Satria, Bara Cakra Yudha; Yudha, I Made Kusuma (LPPM Universitas Jambi, 2026)
Deforestation remains a major socio-environmental problem because forest conversion often remains economically attractive despite its widely recognized ecological and social costs. This study examines how profit-seeking helps explain decisions that lead to forest loss and considers how conservation-oriented choices can be strengthened without neglecting livelihood needs. Using a qualitative literature review and document analysis of foundational economic texts, peer-reviewed studies on deforestation, environmental behavior research, and policy reports on sustainable forest governance, the study identifies four recurring patterns. First, forests are often treated as assets that can be converted into short-term income through timber extraction, agricultural expansion, infrastructure development, and land speculation. Second, Adam Smith’s concept of self-interest helps explain why actors prioritize immediate economic returns, but it does not fully account for environmental decision-making, which is also shaped by institutions, social norms, moral responsibility, and education. Third, profit-seeking becomes more damaging where property rights are weak, monitoring is limited, and policy enforcement is inconsistent. Fourth, conservation outcomes tend to improve when economic incentives are restructured through community forestry, payments for ecosystem services, and livelihood-oriented sustainable development strategies. This study contributes to debates on forest governance by showing that deforestation is shaped not by profit alone, but by the interaction of economic motivation, institutional conditions, and ethical regulation.